Narcotic Free Cervical Endocrine Surgery: A Shift in Paradigm. Issue 2 (August 2021) - Ruffolo, Luis I.; Jackson, Katherine M.; Juviler, Peter; Kaur, Roma; Chennell, Todd; Glover, Danielle M.; Linehan, David C.; Moalem, Jacob
Abstract : Background and Objective: The opioid epidemic has stimulated initiatives to reduce the number of unnecessary narcotic prescriptions. We adopted an opt-in prescription system for patients undergoing ambulatory cervical endocrine surgery (CES). We hypothesized that empowering patients to decide whether or not to receive narcotics for pain control would result in fewer unnecessary opioid prescriptions. Methods: We enrolled all patients scheduled for outpatient CES between July 2017 and June 2018 in a narcotic opt-in program. Patient demographics, procedure characteristics, and postoperative pain scores were collected prospectively. Statistical analyses were performed to correlate clinical predictors with narcotic request. Results were compared against a historical control group. The study was approved by the University IRB. Results: A total of 216 consecutive patients underwent outpatient CES following implementation of the program. Only nine (4%) requested prescription narcotic medication at discharge, and no patient called after discharge to request analgesic medications. Compared with our prior treatment paradigm, we achieved a 96.6% reduction in the number of narcotic tablets prescribed, and a 98% reduction in unconsumed tablets. Univariate analysis suggested history of substance abuse ( P < 0.001), anxiety ( P = 0.01), depression ( P < 0.001), baseline narcotic use ( P = 0.004), highest pain postoperatively ( P = 0.004), and incision length ( P = 0.007) as predictive for narcotic request. Multivariate analysis retained significance with incision length and history of substance abuse. Conclusion: By empowering patients undergoing ambulatory CES to accept or decline a prescription, we reduced the number of prescribed narcotic tablets by 96.6%. Although longer incisions and prior substance abuse predict higher likelihood of requesting pain medication on discharge, 207 of 216 patients were treated with acetaminophen alone.